2018
DOI: 10.1038/s41598-018-29589-y
|View full text |Cite
|
Sign up to set email alerts
|

Alpha B-crystallin C-802G polymorphism and colorectal cancer susceptibility and clinical outcome in Chinese population

Abstract: Colorectal cancer (CRC) is one of the most prevalent cancers worldwide and Alpha B-crystallin (CRYAB) protein has been identified as a prognostic biomarker for CRC. We evaluated CRYAB C-802G (rs14133)polymorphism in association with CRC risk and survival in Chinese population. We genotyped for CRYAB C-802G (rs14133), A-1215G (rs2228387) and intron 2 (rs2070894), and assessed their associations with CRC in a case-control study of 441 CRC cases and 500 healthy controls. We also analyzed this polymorphism in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…(2018) studied CRYAB C-802G (rs14133) polymorphism in association with colorectal cancer risk and survival. CG/GG genotype carriers were associated with increased risk of CRC in comparison of CC genotype carriers [101].…”
Section: Annals Of Agricultural and Environmental Medicinementioning
confidence: 89%
“…(2018) studied CRYAB C-802G (rs14133) polymorphism in association with colorectal cancer risk and survival. CG/GG genotype carriers were associated with increased risk of CRC in comparison of CC genotype carriers [101].…”
Section: Annals Of Agricultural and Environmental Medicinementioning
confidence: 89%
“…Considering the potential association of SNPs with congenital cataract and the dearth of information on genetic association studies using intronic SNPs,[ 38 39 ] the present study was performed to understand the distribution of intronic SNPs rs3788059 ( CRYAA ), rs2070894 ( CRYAB ), rs2071861 ( CRYBA4 ), rs5752083 ( CRYBB2 ), and rs5996863 ( CRYBB2 ) in congenital cataracts and normal healthy controls. Although association studies using these markers have never been reported in congenital cataracts, studies on rs2070894 concerning colorectal and oral cancer[ 40 41 ] and rs2071861 concerning high myopia[ 42 43 ] have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…(2011)[ 40 ] and Wu et al . (2018)[ 41 ] evaluated the association of CRYAB -rs2070894 polymorphism with colorectal and oral cancer, respectively, and did not report any significant association of the allele or genotype with the disease. The distribution of the “AC” genotype of CRYBB2 -rs5752083 was found to be significantly less in cases than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, CRYAB may trigger the EMT in CRC by activating the ERK signaling pathway and is a potential tumor biomarker for CRC diagnosis and prognosis 108. Also, CG/GG at CRYAB C-802G is correlated with CRC susceptibility, and this polymorphism may be a useful marker for the clinical outcome of CRC 112…”
Section: Cryab In Diseasesmentioning
confidence: 98%